2017
DOI: 10.1016/j.scitotenv.2017.02.100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stormflow and baseflow phosphorus pressures on stream ecology in agricultural catchments

Abstract: Stormflow and baseflow phosphorus (P) concentrations and loads in rivers may exert different ecological pressures during different seasons. These pressures and subsequent impacts are important to disentangle in order to target and monitor the effectiveness of mitigation measures. This study investigated the influence of stormflow and baseflow P pressures on stream ecology in six contrasting agricultural catchments. A five-year high resolution dataset was used consisting of stream discharge, P chemistry, macroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 46 publications
1
34
0
2
Order By: Relevance
“…Other studies also found urbanization to be strongly negatively linked to aquatic ecology (King et al, 2011; Teittinen et al, 2015; Golden et al, 2016; Herrero et al, 2018). This negative association with urban land cover may be linked to additional pollutants associated with surface runoff as well as more bioavailable nutrients from point sources (Ekholm and Krogerus, 2003; Ekholm et al, 2009; Richards et al, 2016; Stutter et al, 2018) likely to have a greater impact on river ecology (Shore et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found urbanization to be strongly negatively linked to aquatic ecology (King et al, 2011; Teittinen et al, 2015; Golden et al, 2016; Herrero et al, 2018). This negative association with urban land cover may be linked to additional pollutants associated with surface runoff as well as more bioavailable nutrients from point sources (Ekholm and Krogerus, 2003; Ekholm et al, 2009; Richards et al, 2016; Stutter et al, 2018) likely to have a greater impact on river ecology (Shore et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…The qualitative status of European waterbodies under the Water Framework Directive (WFD) [1] is determined relative to fixed quantitative thresholds of chemical concentration and physical/ecological status. Monitoring at the outlets of agricultural catchments has revealed that concentrations of nutrients, particularly phosphorus (P), in stream water become elevated during low-flow conditions and may exceed legislated thresholds [2,3]. Such elevated concentrations, while not necessarily reflective of the mean quality of the stream over the entire course of the year, may occur at critical times affecting the ecological health of indicator species such as macroinvertebrates and diatoms [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring at the outlets of agricultural catchments has revealed that concentrations of nutrients, particularly phosphorus (P), in stream water become elevated during low-flow conditions and may exceed legislated thresholds [2,3]. Such elevated concentrations, while not necessarily reflective of the mean quality of the stream over the entire course of the year, may occur at critical times affecting the ecological health of indicator species such as macroinvertebrates and diatoms [2,4]. It has been observed that low temporal resolution monitoring can lead to ambiguity in status classification [5] and in load estimation [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an important portion of streamflow that generates from shallow, lateral subsurface flow and deep groundwater flow and changes gradually over short‐ and long‐term scales (Nathan & McMahon, ; Rumsey, Miller, Schwarz, Hirsch, & Susong, ). Baseflow sustains river flow between events affected by rainfall–run‐off processes (Miller, Buto, Susong, & Rumsey, ; Shore et al, ; J. Zhang, Zhang, Song, & Cheng, ), which is important for understanding relationships between aquatic habitats and their environment (Ford, King, & Williams, ; Santhi, Allen, Muttiah, Arnold, & Tuppad, ). Knowledge about baseflow can improve the understanding of catchment streamflow partitioning (Mei & Anagnostou, ; Ravazzani, Gattinoni, Valentina, & Rosso, ), relieving flood events (Kinkela & Pearce, ), assessing surface–groundwater flow interactions (Arnold, Muttiah, Srinivasan, & Allen, ; Lamontagne, Leaney, & Herczeg, ; L. Zhang, Brutsaert, Crosbie, & Potter, ), and aiding water resource management (Arciniega‐Esparza et al, ; Arnold, Allen, Muttiah, & Bernhardt, ; Z. Dai, Chu, Du, Stive, & Hong, ).…”
Section: Introductionmentioning
confidence: 99%